Power Of Forgiveness In Dave Pelzer's A Man Named Dave (1999): A Psychoanalytic Criticism - Sari, Dewi Puspita, Dr. Phil. Dewi Chandraningrum, S. Pd, M. Ed, Drs. Abdillah Nugroho, M.Hum (2013)
The object of this study is A Man Named Dave novel directed by Dave Pelzer. The major problem in this study is how the major character proves his power of forgiveness in A Man Named Dave (1999) novel by Dave Pelzer. This study focused on the one of the major characters namely Dave Pelzer, using the mean of structural element and psychoanalytic analysis. The object of this study is A Man Named Dave novel published in 1999. There are two objectives of the study. First is to analyze the novel based on the structural elements by finding characters and characterizations, setting, point of view, plot, and theme. Second is to analyze Dave's forgiveness in the novel based on Freud's principles of psychoanalytic, such as the id, ego and superego. The type of this study is descriptive qualitative. The data source in this research is divided into two types that are primary data and secondary data. Primary data source is the novel A Man Named Dave and the secondary data source is books or any information related to the practice in power of forgiveness that support the psychoanalytic approach by Sigmund Freud. The technique of analyzing data in this research paper is descriptive. The outcome of the study shows that the problem faced by the major character Dave Pelzer causes the conflict of his mental condition.